2002
DOI: 10.1002/jemt.10110
|View full text |Cite
|
Sign up to set email alerts
|

Immune response by host after allogeneic chondrocyte transplant to the cartilage

Abstract: Chondrocytes constitutively express class I and, in some species, class II major histocompatibility complex (MHC). It is also possible that they possess specific differentiation antigen(s). Furthermore, lymphocytic cells, corresponding to NK cells, display spontaneous cytotoxic activity against chondrocytes. Studies on articular cartilage repair by transplants of allogeneic chondrocytes were mainly done on non-inbred animals, such as rabbits and hens. Surprisingly, only in single instances these transplants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 85 publications
(108 reference statements)
2
42
1
1
Order By: Relevance
“…The lack of SLA II in integrins may be counteracting the effect of the VCAM-1 blockade on U937 adhesion to hTNF-α-stimudetection after the cytokine treatments was unexpected as MHC class II is expressed in human and other mamlated PCC at a high E/T ratio. Overall, our results indicate that PCC bind U937 through at least pVCAM-1 and malian chondrocytes (24) and in PAEC activated with hTNF-α (2,6). Nevertheless, these results are consistent the Gal antigen.…”
Section: Pcc Secrete Pil-8 and Pil-6 In Response Tomentioning
confidence: 61%
See 2 more Smart Citations
“…The lack of SLA II in integrins may be counteracting the effect of the VCAM-1 blockade on U937 adhesion to hTNF-α-stimudetection after the cytokine treatments was unexpected as MHC class II is expressed in human and other mamlated PCC at a high E/T ratio. Overall, our results indicate that PCC bind U937 through at least pVCAM-1 and malian chondrocytes (24) and in PAEC activated with hTNF-α (2,6). Nevertheless, these results are consistent the Gal antigen.…”
Section: Pcc Secrete Pil-8 and Pil-6 In Response Tomentioning
confidence: 61%
“…The studies of pCD40 have focused on its effect on PAEC, but pCD40 may well participate in to cytokine-induced apoptosis, we also observed a higher resistance in the case of PCC. In addition, cartilage is the activation of human T cells as an anti-hCD154 mAb displays an inhibitory effect in coculture experiments known to have some immune privilege properties that need further clarification (24). Thus, these particularities (35).…”
Section: Pcc Secrete Pil-8 and Pil-6 In Response Tomentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of NK cells to graft rejection is increasingly being acknowledged in allotransplantation (9,10). Interestingly, a potential role of NK cells in the rejection of transplanted allogeneic chondrocytes has been suggested (11). However, recent findings indicate that NK cells may play a more prominent role in the rejection of xenografts than allografts (12,13).…”
mentioning
confidence: 99%
“…Graft subsidence has actually been observed at 2-3 years status postindex surgery and is likely because of a delay in early revascularization as a result of the immune response and softened subchondral bone. Basic animal research has shown the importance of isolation of allogenic chondrocytes from post subchondral bone [57] (Figure 7). …”
Section: Allograftmentioning
confidence: 99%